Từ tín hiệu đến hoài nghi: Vai trò điều tiết của niềm tin người tiêu dùng trong tác động của quảng cáo ESG đến ý định mua - Lê Thị Hồng, Minh; Đặng Thái, Thịnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines how advertising related to Environmental, Social, and Governance (ESG) influences consumer purchase intention and investigates the moderating role of consumer trust. Signal theory and the persuasion knowledge model are integrated to develop the proposed research framework. Based on an experimental survey of 227 participants, the data were analysed using PROCESS in SPSS. The results indicate that ESG advertising on product packaging and consumer trust both have positive direct effects on purchase intention. However, interaction analysis shows that when trust is low, ESG packaging advertising substantially strengthens purchase intention, whereas the incremental effect of ESG advertising weakens as trust increases and may become negligible at very high levels of trust, reflecting the risk of greenwashing skepticism. The study contributes to the sustainable marketing literature by identifying consumer trust as a critical boundary condition. From a managerial perspective, the findings suggest that brands should tailor ESG messages to the trust level of their target customers to maximise communication effectiveness and minimise skepticism.
Keywords: Greenwashing skepticism; Purchase intention; Consumer trust; ESG advertising